Investigation of Supply Chain Integration Performance in Export-focused Manufacturing Industry in China and An Assessment of A Local Gymnastic Products Manufacturer - Zhang, Chong (2008)
The purpose of this dissertation is try to find out the gap between exported-focused Chinese manufacturing industry practice with world-class supply chain integration performance in developed countries. This is helpful to reveal and explain difficulties and obstacles that limit local suppliers to pursue better supply chain performance. A case study is used to analyze performance of a specific Chinese producerÃÂ¢ÃÂÃÂs supply chain and operations management. The results found out that widely deficiency of SCM and integration education, insufficient self-position in supply chain, unenlightened technology infrastructures and management are major reasons for general export-focused manufacturing industry. Refer to the case study company, key quality issue is derived from irrational and ineffective supplier management, loose quality control during production process. Late delivery performance is originated from time-consuming prototype confirmation, raw material/components quality and/or delivery delay and inefficient operations management.